1976
DOI: 10.1007/bf01973267
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of bradykinin in the pulmonary circulation

Abstract: Bradykinin is very efficiently inactivated on passage through the pulmonary circulation by enzymes on the vascular walls. Several different cleavages of the bradykinin molecule have been observed; one appears to be due to angiotensin converting enzyme. Several types of inhibitors have been useful in the study of these pulmonary peptidases and have helped increase understanding of the functioning of the angiotensin and plasma kinin systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…2,3 It plays many roles in pathophysiology, particularly as an initiator of inflammation. 4,5 This peptide exerts biological effects by binding to specific G-protein-coupled receptors 6 (B2) on the cell membrane, thereby triggering a series of poorly understood biochemical events that are manifested by pain, 7 contraction of smooth muscle, lowering of arterial pressure, 8 etc. Interactions of bradykinin with natural as well as artificial membranes are extensively investigated in order to elucidate the mechanism of the physiological activity of the peptide by several spectroscopic studies including CD, 9-11 13 C-and 1 H-NMR, [10][11][12] laser Raman spectroscopy, 13 and electron spin resonance spectroscopy, 14,15 The results suggested that the peptide's biological activity could be correlated with the extent of its interaction with the vesicles, supporting the hypothesis of an active role of the membrane as a catalyst for peptide-receptor interaction.…”
mentioning
confidence: 99%
“…2,3 It plays many roles in pathophysiology, particularly as an initiator of inflammation. 4,5 This peptide exerts biological effects by binding to specific G-protein-coupled receptors 6 (B2) on the cell membrane, thereby triggering a series of poorly understood biochemical events that are manifested by pain, 7 contraction of smooth muscle, lowering of arterial pressure, 8 etc. Interactions of bradykinin with natural as well as artificial membranes are extensively investigated in order to elucidate the mechanism of the physiological activity of the peptide by several spectroscopic studies including CD, 9-11 13 C-and 1 H-NMR, [10][11][12] laser Raman spectroscopy, 13 and electron spin resonance spectroscopy, 14,15 The results suggested that the peptide's biological activity could be correlated with the extent of its interaction with the vesicles, supporting the hypothesis of an active role of the membrane as a catalyst for peptide-receptor interaction.…”
mentioning
confidence: 99%
“…Primary inactivation of BK in vivo is accomplished by pulmonary angiotensin I converting enzyme (ACE, kininase II), which destroys more than 99% of BK in a single passage through the pulmonary circulation (Stewart, 1976). ACE cleaves BK at the 7 -8 bond, yielding a totally inactive heptapeptide, which can be cleaved further by ACE.…”
Section: Discovery Of Bradykinin Antagonistsmentioning
confidence: 99%